Adolescent obesity and ANGPTL8: correlations with high sensitivity C-reactive protein, leptin, and chemerin - Hammad, Maha M.; Channanath, Arshad M.; Abu-Farha, Mohamed; Rahman, Abdur; Al Khairi, Irina; Cherian, Preethi; Alramah, Tahani; Alam-Eldin, Nada; Al-Mulla, Fahd; Thanaraj, Thangavel Alphonse; Abubaker, Jehad (Frontiers in Endocrinology, 2023)
Angiopoietin-like proteins (ANGPTLs) mediate many metabolic functions. We had recently reported increased plasma levels of ANGPTL8 in obese adults of Arab ethnicity. However, data on ANGPTL8 levels in adolescent obesity is lacking. Arab population is characterized by a rapid transition, due to sudden wealth seen in the post-oil era, in lifestyle, food habits and extent of physical activity. We adopted a cross-sectional study on Arab adolescents from Kuwait to examine the role of ANGPTL8 in adolescent obesity. The study cohort included 452 adolescents, aged 11-14 years, recruited from Middle Schools across Kuwait. BMI-for-age growth charts were used to categorize adolescents as normal-weight, overweight, and obese. ELISA and bead-based multiplexing assays were used to measure plasma levels of ANGPTL8 and other inflammation and obesity-related biomarkers. Data analysis showed significant differences in the plasma levels of ANGPTL8 among the three subgroups, with a significant increase in overweight and obese children compared to normal-weight children. This observation persisted even when the analysis was stratified by sex. Multinomial logistic regression analysis illustrated that adolescents with higher levels of ANGPTL8 were 7 times more likely to become obese and twice as likely to be overweight. ANGPTL8 levels were correlated with those of hsCRP, leptin and chemerin. ANGPTL8 level had a reasonable prognostic power for obesity with an AUC of 0.703 (95%-CI=0.648-0.759). These observations relating to increased ANGPTL8 levels corresponding to increased BMI-for-age z-scores indicate that ANGPTL8, along with hsCRP, leptin and chemerin, could play a role in the early stages of obesity development in children. ANGPTL8 is a potential early marker for adolescent obesity and is associated with well-known obesity and inflammatory markers.